The Influence of Profitability and Leverage on Firm Value: The Mediating Role of ESG in the Food and Beverage Industry on the IDX, 2020-2024 - Febri Budiyanti; Krisdiana Krisdiana (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The food and beverage industry in Indonesia is currently undergoing a significant transition toward global sustainability standards amid operational profit pressures and economic fluctuations. This study aims to examine the influence of profitability and leverage on firm value, with Environmental, Social, and Governance (ESG) acting as a mediating variable, focusing on food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research methodology is quantitative, utilizing descriptive and verificative approaches. Through purposive sampling, 13 companies were selected, resulting in 65 panel data observations analyzed using EViews software. The results indicate that, partially, profitability has a positive and significant influence on firm value. This supports Signaling Theory, where efficient equity management serves as a primary indicator for investor valuation. Conversely, leverage does not show a significant impact on firm value. The most crucial finding reveals that the ESG mediation variable is unable to mediate the relationship between financial performance and firm value. This indicates that investors in the Indonesian capital market still prioritize short-term financial fundamentals over sustainability scores. Consequently, ESG transparency currently serves as regulatory compliance rather than a strategic driver of economic value